Early Childhood Education For Sustainable Development in Portugal - Folque, Maria Assunção (2017)
This chapter reports on the Portuguese trial of the Environmental Rating Scale for Sustainable Development in Early Childhood (ERS-SDEC) scale which was carried out in the context of the initial training of pre-school teachers at the University of Évora and during their practicum in local pre-schools. The particular context of this trial in initial teacher education provides a particular focus on the professional development of the students, and the cooperating teachers provided by their engagement in a collaborative action-research project that was focused upon Education for Sustainable Development. After providing some Portuguese contextual elements related with ESD, we will report on the trial of the scale in Évora and its results in terms of improving the quality of classroom practices and students and teachers professional development provided by their participation in the project. Finally we will share some reflections on the project, the format and use of the scale and on some critical issues that we learned to be critical in terms of ESD in Early Childhood.